The Experiences of Caregivers of Persons Living with Dementia in Jamaica during COVID-19. (1st August 2021) - Stubbs, Marissa; Govia, Ishtar; Robinson, Janelle N.; Amour, Rochelle; Freeman, Emily
This article provides descriptive insights of the experiences of family caregivers of persons living with dementia during the COVID-19 pandemic. Data were generated as part of a qualitative cross-national project to explore the costs and consequences of providing unpaid dementia care. Participants in Jamaica, who were recruited using community gatekeepers, information booths at health fairs, conferences, and other outreach events, were contacted by telephone to discuss their experiences of the pandemic. When face-to-face in-depth interview data collection was suspended due to the pandemic, ethical approval was received to contact all research participants who were informal unpaid family caregivers, both those whose care recipients had died and those who were active caregivers ( N = 19). Participants in this study were the 10 active family caregivers ( n F = 8; aged 45+; 60% from high socio-economic status). Their updates and reflections during these calls were documented in fieldnotes and analyzed for key themes. Data showed that the pandemic has illustrated the direct costs, both financial and otherwise, that informal dementia carers bear in Jamaica. It also intensified pre-existing challenges faced by family carers. We provide recommendations for sustainable support for family carers.